Fatigue analysis of a cracked shaft: A finite element modeling approach - Thinesshwaran, Gunasekaran; Muhamad Husnain, Mohd Noh; Mohd Akramin, Mohd Romlay; Mohd Shamil, Shaari; Takahashi, Akiyuki (Institute of Physics, 2024)
Shafts are typically used in sophisticated mechanisms and machinery which highly depend on shafts for rotatory motion which could lead to the failure. In today's contemporary, damages caused by cracking on mechanical components and structures have increased, causing crack and structural failure. The failure could be examined by the calculation of stress intensity factor (SIF). Once the shaft reaches the critical SIF (SIFIC), the flaw is initiated and has a potential to propagate upon loading. Typically, the flaw would spread in many patterns and tenders to the formation and initiation of different types of cracks. Thus, the objective of this research work is to analyse fatigue cracked shafts. Prediction of crack growth via SIF calculation. SIF is usually adapted to predict the stress intensity near the crack tip where crack propagation occurs. Thus, SIF is used to study and analyse the cracked surface in relation to crack initiation and propagation. The SIF is calculated through finite element method (FEM) since the FEM is capable simulating complex geometry. The SIF is calculated based on the deformation in FEM calculation. The results show the predicted crack propagation and SIF calculation. It is crucial to study the resistance of cracked shafts towards cyclic loading for maintenance preceding and retirement of the structure.